2007
DOI: 10.4269/ajtmh.2007.77.1028
|View full text |Cite
|
Sign up to set email alerts
|

Year-to-Year Variation in the Age-Specific Incidence of Clinical Malaria in Two Potential Vaccine Testing Sites in Mali With Different Levels of Malaria Transmission Intensity

Abstract: To explore the feasibility of field sites for malaria vaccine trials, we conducted a prospective study of clinical malaria incidence during two consecutive transmission seasons in children and young adults living in two areas of Mali with different entomologic inoculation rates (EIRs). Approximately 200 subjects (3 months to 2 years of age) were enrolled per site and followed weekly. Malaria smears were performed monthly in all participants and when symptoms or signs of malaria were present. In Sotuba (annual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 14 publications
(13 reference statements)
4
34
1
Order By: Relevance
“…12,14,[23][24][25][26] Early studies in western Uganda suggested that at high altitudes, the parasite rate in persons less than 20 years of age old was nearly twice as high as in those persons 20 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…12,14,[23][24][25][26] Early studies in western Uganda suggested that at high altitudes, the parasite rate in persons less than 20 years of age old was nearly twice as high as in those persons 20 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Malaria incidence in 2000 was 0.8 in 0-5 year olds and 1.3 in 6-10 year olds. 17 Kollé is situated 55 km south of Bamako and is a typical rural Savannah village with a population of ∼2,500 (Figure 1; Sotuba and 176 mm in Kollé, during the subsequent dry season hardly any rain fell with on average 5 mm and 3 mm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The entomological inoculation rate is 4-12 infective bites per person per year. 17 Kolle is a village of 2,500 inhabitants located 57 km southwest of Bamako in the Sudan savanna area and 9 km away from the Niger River. The entomological inoculation rate is nearly identical to the level of Banambani.…”
Section: Methodsmentioning
confidence: 99%
“…The entomological inoculation rate is 137-167 infective bites per person per year. 17 Sotuba is a peri-urban area of Bamako with 6,472 inhabitants. The entomological inoculation rate is 4-12 infective bites per person per year.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation